2020
DOI: 10.1109/rbme.2019.2949749
|View full text |Cite
|
Sign up to set email alerts
|

Robots and Tools for Remodeling Bone

Abstract: The field of robotic surgery has progressed from small teams of researchers repurposing industrial robots, to a competitive and highly innovative subsection of the medical device industry. Surgical robots allow surgeons to perform tasks with greater ease, accuracy, or safety, and fall under one of four levels of autonomy; active, semi-active, passive, and remote manipulator. The increased accuracy afforded by surgical robots has allowed for cementless hip arthroplasty, improved postoperative alignment followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 104 publications
(130 reference statements)
0
5
0
Order By: Relevance
“…Surgical robotics has seen a significant increase in adoption over the last decade [ 21 ]. In orthopaedics, robots are primarily used to assist with the placement of off-the-shelf implants [ 22 ], and there are limited examples of work completed on the use of robotics for bone tumour excision. Khan et al demonstrated improved accuracy when using a haptic-guided robotic system for planar cuts as compared to manual surgery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical robotics has seen a significant increase in adoption over the last decade [ 21 ]. In orthopaedics, robots are primarily used to assist with the placement of off-the-shelf implants [ 22 ], and there are limited examples of work completed on the use of robotics for bone tumour excision. Khan et al demonstrated improved accuracy when using a haptic-guided robotic system for planar cuts as compared to manual surgery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that surgical robots are capable of performing intraoperative tasks with a high degree of precision [16][17][18][19], as well as following complex nonplanar and curvilinear paths for approaches that would not be possible to perform accurately or safely freehand. Khan et al evaluated the deviation from a planned multi-planar osteotomy, comparing the accuracy of freehand unassisted sawing against the same cuts performed with robotic assistance.…”
Section: Introductionmentioning
confidence: 99%
“…In response to this problem, many novel technologies to localize distal locking holes, have been invented, such as electromagnetic navigation technology 4 , computer-aided navigation technology 5 , orthopedic robots 6 and so on. However, these technologies (including traditional freehand technique 7 ) still have some limitations, such as inaccurate positioning, low first success rate, high demand for expensive equipment, long learning curve of surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…However, these technologies (including traditional freehand technique 7 ) still have some limitations, such as inaccurate positioning, low first success rate, high demand for expensive equipment, long learning curve of surgeons. 6–13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation